Social modulation of fear: Facilitation vs buffering - Morozov, Alexei (Genes Brain Behav, 2018)
Social behaviors largely constitute mutual exchanges of social cues and the responses to them. The adaptive response also requires proper interpretation of the current context. In fear behaviors, social signals have bidirectional effects—some cues elicit or enhance fear whereas other suppress or buffer it. Studies on the social facilitation and social buffering of fear provide evidence of competition between social cues of opposing meanings. Co-expression of opposing cues by the same animal may explain the contradicting outcomes from the interaction between naive and frightened conspecifics, which reflect the fine balance between fear facilitation and buffering. The neuronal mechanisms that determine that balance provide an exciting target for future studies to probe the brain circuits underlying social modulation of emotional behaviors.